2020
DOI: 10.1177/1078155220940396
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma and bevacizumab in elderly patients: Monocentric study

Abstract: Purpose A retrospective monocentric comparison of progression-free survival, overall survival, clinical benefit and tolerability between elderly (age>70) and non-elderly (age ≤ 70) patients receiving bevacizumab for recurrent glioblastoma. Methods We analyzed 47 patients with recurrent glioblastoma receiving bevacizumab (10 mg/kg every 14 days) between January 2011 and January 2014. Bevacizumab was introduced for all patients at recurrence after a first-line treatment by temozolomide. Results Nineteen patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a retrospective study, the efficacy and safety of bevacizumab in recurrent glioblastoma appear similar in elderly and non-elderly patients. However, the clinical benefit seemed less evident in younger patients ( 68 ).…”
Section: Managements Of Recurrencementioning
confidence: 97%
“…In a retrospective study, the efficacy and safety of bevacizumab in recurrent glioblastoma appear similar in elderly and non-elderly patients. However, the clinical benefit seemed less evident in younger patients ( 68 ).…”
Section: Managements Of Recurrencementioning
confidence: 97%
“… [ 72 ] Age groups 2009, Nghiemphu et al Retrospective study rGBM 123 (100%) BEV combined therapy BEV containing regimen vs. non-BEV regimen BEV treatment reflected a significant increase in PFS and OS, compared with the control group [ 99 ] 2021, Barrascout et al Retrospective study rGBM 47 (100%) BEV monotherapy BEV Significant improvement based on the KPS scale was observed in non-elderly patients. [ 48 ] Laboratory examinations 2016, Bertaut et al Retrospective study rGBM 265 (100%) BEV-containing regimen BEV-containing regimen Only patients with a high neutrophil count (> 6 G/L) benefited from the BEV-containing regimens. [ 100 ] 2019 Quillien et al Prospective study rGBM 29 (100%) BEV monotherapy BEV Low neutrophil counts (< 3.9 G/L) and high Treg counts (above 0.011 G/L) had prolonged OS.…”
Section: Resultsmentioning
confidence: 99%
“…No consensus was found regarding the association between BEV efficacy and age groups. Two retrospective studies found that there was a better improvement in non-elderly patients with rGBM/recurrent high-grade glioma (rHGG) patients compared with elderly patients treated with BEV-containing regimens [ 47 , 48 ]. However, another retrospective study concluded controversially that elderly patients had more prognostic benefits compared with younger patients [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bevacizumab is not recommended for people with newly diagnosed glioblastoma due to high rates of adverse events and no improvement in overall survival [79][80][81]. In select cases, bevacizumab may be cautiously used to treat tumor-related edema and to avoid the side-effects of steroids.…”
Section: Chemotherapymentioning
confidence: 99%